(3SdWI GdEOGQI aj JYOjd YbhO GdCTZGd GdYGeI habG dfXGe ChGeQ GdJZjjQ (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdeUQj h YbhO GdEfTGAGJ GdfehPLjI (B/ s - (3eMeO aDGO eMeO GdMQjQjs; (3eMeO eMeO HOQGf (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2010)
(3JJfGhd GdQSGdI SdWI GdEOGQI aj JYOjd YbhO GdCTZGd GdYGeI habG dfXGe ChGeQ GdJZjjQ(B: (3h gi OQGSI ebGQfI Hjf GdbGfhf GdeUQj h YbhO GdEfTGAGJ GdfehPLjI(B: (3h Ydi GdCNU YbhO GdajOjc GdfehPLjI GdJj JCKQJ UjGZJgG HeHGOF GdfXGe GdbGfhfj GdGfLdjRj(B. (3h JhVM gPg GdQSGdI eaghe ChGeQ GdJZjjQ h OhQgG GdMjhj aj YbhO GdEfTGAGJ(B: (3ceG JMOO UhQ ChGeQ GdJZjjQ h VhGHW GdMb aj EUOGQgG(B: (3Ke JHjf cjajI eeGQSI QH GdYed dMbg aj JYOjd YbhO GdEfTGAGJ HEQGOJg GdefaQOI ef NdGd EUOGQ gPg GdChGeQ(B. (3ceG JhVM eOi GdJRGe GdebGhd HJfajP ChGeQ GdJZjjQ(B: (3h GdLRGAGJ GdeJQJHI Ydi ENdGdg HgPG GdGdJRGes
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2010s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3ChGeQ GdJZjjQs; (3YbhO GdCTZGd GdYGeIs; (3YbhO GdajOjc GdfehPLjIs; (3QSGFd LGeYjIs